Effects of Agrochemicals on Human Health - B Pradhan, Bibhuti; Kanta Behera, Shishira (International Journal of Psychosocial Rehabilitation, 2025)
The industrialization of agricultural segment has increased the chemical pressure on natural ecosystems. Nowadays, agrochemicals are commonly used in food production. Pesticides are agrochemicals used to protect plants and humans from various diseases in urban green areas, agricultural land and public health programs. Farmers use agrochemicals to monitor weed growth and to prevent insects, moulds and rodents from destroying crops. The extreme use of agrochemicals has led to growing concerns about the adverse effects on environment and the human health. The continued use of agrochemicals against disease vectors and agricultural pests presents serious threats to human health as well as the environment. The periods and levels of exposure to agrochemicals, the types of agrochemicals used (in terms of toxicity and persistence) and the different environmental conditions of the areas are also some of the factors for acute and chronic human health and environmental poisoning. Farmers should use alternative methods such as integrated pest management (IPM), organic farming or crop rotation to avoid contamination of foods with agrochemicals. Consumers should also have organic food products in order to get away from the harmful effects of agrochemicals. However, their side effects can be an important factor in environmental health risk because of their known ability to cause a large number of negative environmental and health effects.